Performance Evaluation of the Optimized Design Ratio Between the Diameters of the Basin and Curved Blade in the Gravitational Water Vortex Turbine - BOISER, Christie Claire D.; CARPIO, Lance Arthur Lim; CELERINOS, Philip Jun S.; LEE, Joven Dy S.; PINILI, Gary G. (Engineering Transactions, 2025)
The key role of the gravitational water vortex turbine (GWVT) is to generate electricity to support modern civilization in their essential daily needs by harnessing kinetic energy from flowing water. With this, the lack of access to electricity can be addressed by utilizing the potential of the Philippines’ abundant bodies of water. This study evaluates the impact of low-density turbine blades on the GWVT with reference to the selected parameters: rotational speed and mechanical efficiency. The ANSYS simulation and laboratory test both found that the 0.55 ratio between the diameters of the nylon rod blade and the optimized basin with guide vanes achieved the highest rotational speed of 205.95 RPM and 120.1 RPM, respectively. Conversely, the design with a 0.60 ratio between the diameters of the steel blade and the normal basin provided optimum performance, achieving an average of 98.2 RPM and the highest mechanical efficiency of 43.75%, thereby preventing energy loss and maximizing output performance. Results also indicated a significant difference in the performance of the GWVT using the normal basin compared to the optimized basin with guide vanes. Lastly, there was a considerable difference in the performance of the GWVT for the design ratios of 0.55, 0.60, and 0.65 for the runner blade and basin, and further analysis showed that torque and rotational speed have a linear relationship. Thus, this study could serve as a benchmark for identifying alternative materials and optimizing the design of GWVT to help improve power generation using hydropower as a source of electricity.